Modelo de gestão de resíduos sólidos para a Vila Rural Flor do Campo no município de Campo Mourão - PR - Palazzo, Mateus Leme Varajão (2015)
This study completion course aimed to propose a model of integrated management of solid waste in Vila Rural Flor do Campo, in the municipality of Campo Mourao. In this way, they were initially conducted field visits and semi-structured interviews with community residents. The visits were conducted in order to obtain a current overview of the current waste management conditions. The interviews with residents provided information about the socioeconomic profile and practices in managing local waste and possible participation of the government in the community. In general the results generated verified the absence of waste management in Vila Rural, improper practices in the management of waste and lack of knowledge on the subject. It was also found a low solid waste generation per capita, with 0.323 kg / person / day, due to the use of organic waste in animal nutrition in order to increase soil fertility. Either way, it was possible to identify a waste recovery potential, especially the share of recyclable and organic fraction, each of which accounted for 23.41% and 52.55% respectively of the total amount of waste generated in Vila Rural. The compilation and analysis of the proposed management model was based on the reuse, recycling and composting of waste created, coupled with environmental education campaigns and restoration of the link with those involved in municipal waste management.